2019
DOI: 10.1108/ci-04-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

An overview of benefits and challenges of building information modelling (BIM) adoption in UK residential projects

Abstract: This paper sets out to present a state-of-the-art review of Building Information Modelling (BIM) in the UK construction practice. In particular, the aim is to examine the scope, value and practical implications of BIM implementation in residential projects by evaluating practitioners' perspectives working in the Greater London Area (GLA). The paper outlines the general status quo of BIM adoption and maturity in the UK. It then discusses the feasibility of BIM use in residential projects drawing on an online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 45 publications
0
63
0
2
Order By: Relevance
“…This tradition has been established to affect the construction industry in general ( [32] since inception when compared to other industries like the manufacturing industry. Defending this tradition, [33] claimed that the uptake of new tools, techniques, and methods requires significant time, skills and capital investment. These factors outlined by [33] were discussed in a cursory manner in the context of BIM adoption in developing countries.…”
Section: Bim Adoption In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…This tradition has been established to affect the construction industry in general ( [32] since inception when compared to other industries like the manufacturing industry. Defending this tradition, [33] claimed that the uptake of new tools, techniques, and methods requires significant time, skills and capital investment. These factors outlined by [33] were discussed in a cursory manner in the context of BIM adoption in developing countries.…”
Section: Bim Adoption In Developing Countriesmentioning
confidence: 99%
“…Defending this tradition, [33] claimed that the uptake of new tools, techniques, and methods requires significant time, skills and capital investment. These factors outlined by [33] were discussed in a cursory manner in the context of BIM adoption in developing countries. This study viewed the three factors under two perspectives: capital investment (an economic-related factor) and time and skills (actor-dependent factors).…”
Section: Bim Adoption In Developing Countriesmentioning
confidence: 99%
“…Future built environment professionals will challenge the conventions of the past and will use their creative and innovative capacities. From a learning front engaged with digital technology, it is now possible to embrace new collaboration models that change the paradigms in fundamental ways (Bryde et al, 2013; Georgiadou, 2019; Özorhon and Karaciğan, 2020; Stanley and Thurnell, 2014). But this pedagogical change is not about technology per se; nor is it about distance learning, or the ability of students to access lectures by some of the world’s leading professors from free online sites; rather, this represents a change in the relationship between student and teacher in the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, BIM biggest input was the capacity for modernizing models in actual time, remove conflicts, examine alterations during initiate design phase and interchange precious project data in the project lifespan. This allow effective dispute settlement within project team and enhance collaboration among the project participants (Georgiadou, 2019). Arayici, Egbu and Coates (2012) identified that a thorough BIM model and an overall and updated cost database is needed to reach the greatest efficiencies.…”
Section: Improved Visualization For Better Understanding Of Designs For Measurement and Minimise Omissionsmentioning
confidence: 99%